2019
DOI: 10.1097/bot.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Long-Term Outcomes and Avoiding Failure With the Fibula Intramedullary Nail

Abstract: Objectives: To identify risk factors for fixation failure, report patient outcomes and advise on modifications to the surgical technique for fibula nail stabilisation of unstable ankle fractures.Design: Retrospective review.Setting: Orthopaedic trauma unit serving a capital city.Patients: All 342 patients were identified retrospectively from a prospectively collected singlecentre trauma database over a nine-year period.Intervention: Unstable ankle fractures managed surgically with a fibula nail. Main Outcome M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Surprisingly, some of the SF-36 scales in our series trended even higher than in the normative patient population. The safety data recorded in this study are also in line with recent publications reporting relatively low complication rates associated with the use of a locked intramedullary fibular nail [20][21][22][23].…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, some of the SF-36 scales in our series trended even higher than in the normative patient population. The safety data recorded in this study are also in line with recent publications reporting relatively low complication rates associated with the use of a locked intramedullary fibular nail [20][21][22][23].…”
Section: Discussionsupporting
confidence: 89%
“…This finding may be attributed to closed reduction and limited axial instability in IMN surgery, which are consistent with those of previous studies suggesting that suboptimal fracture reduction of the fibula is one of the major factors for PTOA. 5,9-11,26 Particularly, in a logistic regression analysis, the presence of posterior malleolar fracture as well as Weber’s type C injury was found to be a risk factor developing PTOA in the IMN group. As mentioned above, posterior malleolar fracture has been reported as a major determinant of tibiotalar load transfer, posterior talar stability, and rotatory ankle stability.…”
Section: Discussionmentioning
confidence: 88%
“…According to recent studies, the new-generation interlocking nailing device of the fibula we used has been reported to achieve satisfactory reduction comparable to the plate. 2,9-11,20,43 Moreover, in a recent meta-analysis, the mean rate of malunion after fibular IMN surgery was 3.6% (0%-6.7%) of the patients. 38 However, in our study, poor reduction at final follow-up was observed in 16.0% of patients treated with the fibular IMN as assessed using plain radiography and 20.3% as assessed using 3D-reconstructed CT, both of which are inferior to the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Considering the differences in injury severity and complication rates, the benefits of fibula IMN fixation of malleolar ankle fractures may be even more pronounced in pilon fractures. 9,10,14,15 Intramedullary fibula fixation of pilon fractures has only been investigated in a few small series. Stewart et al 9 reported on distally locked fibular IMN in 23 pilon fractures and demonstrated a 100% union rate, no wound complications, no revision surgeries, and one symptomatic fibula implant removal.…”
Section: Discussionmentioning
confidence: 99%